(untitled) (Medico Legal Update, 2020)
Poison is any substance which when administered, inhaled or ingested is capable of causing deleterious effects on the human body. This prospective study was carried out involving 353 cases of poisoning admitted in Sri Ramachandra Medical College & Research Institute Porur, Chennai, during the period of June 2014- June 2015. The demographic details were acquired from the patient, relatives, friends or the investigating officer and by going through the medical records and the inquest report. In the current study the maximum cases were in the age group of 20-29 years and the incidence decreased as the age increases and it was evident that the incidence of poisoning is more in case of females when compared to males. The material of maximum abuse was T.Alprazolam (10.8%), followed by Rat Killer poison (9.6%), and followed by Snake Strike (8.8%), Organo Phosphorus Poisoning (8.5%), and Multiple Tablet Overdose (8.2%). 78% consumed poison intentionally and are suicidal in nature, as no cases of homicidal poisoning were reported in the study group, rest of the 22% of cases, were of accidental in nature. Mortality wise analysis showed that dead cases count 13 in number which accounts to 3.5% of all poisoning cases.